2016
DOI: 10.1111/acem.12963
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Reliability of a Novel Palliative Care Screening Tool Among Emergency Department Providers

Abstract: Background: The Palliative Care and Rapid Emergency Screening (P-CaRES) Project is an initiative intended to improve access to palliative care (PC) among emergency department (ED) patients with lifelimiting illness by facilitating early referral for inpatient PC consultations. In the previous two phases of this project, we derived and validated a novel PC screening tool. This paper reports on the third and final preimplementation phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…This is similar to the usability and acceptability testing of other ED palliative care screening tools. For example, 80.5% of emergency providers who tested the P-CaRES tool felt it would be useful for their practice [12], and 70% of providers indicated a content-validated palliative care screening tool developed by Ouchi et al (2017) was acceptable [32]. In contrast, the percentage of encounters that identified palliative care needs from the CDS tool (9%) is much lower compared to the 32% positive screening found during feasibility testing of the Ouchi et al tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to the usability and acceptability testing of other ED palliative care screening tools. For example, 80.5% of emergency providers who tested the P-CaRES tool felt it would be useful for their practice [12], and 70% of providers indicated a content-validated palliative care screening tool developed by Ouchi et al (2017) was acceptable [32]. In contrast, the percentage of encounters that identified palliative care needs from the CDS tool (9%) is much lower compared to the 32% positive screening found during feasibility testing of the Ouchi et al tool.…”
Section: Discussionmentioning
confidence: 99%
“…As an initial step, a scoping review of validated screening tools for unmet palliative care needs in the ED was conducted in March 2018 by author AT utilizing Pubmed. Based on the review, the Palliative Care and Rapid Emergency Screening (P-CaRES) was identified as the only screening tool to meet our search criteria and identify emergency patients with serious, life-limiting illness who could benefit from palliative care services [12]. P-CaRES consists of a two part screening process.…”
Section: Scoping Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of these, one example is represented in Table . Recent research has shown that the use of one such list is acceptable and reliable in the ED setting …”
Section: Initiating Planning In the Patient Approaching End‐of‐lifementioning
confidence: 99%
“…[17][18][19][20] Recent research has shown that the use of one such list is acceptable and reliable in the ED setting. 21 Emergency physicians have a critical circuit breaker role in: (i) identifying patients who would benefit from formal advance care planning; and then (ii) raising the issue at the appropriate time in a non-threatening way. 22 Beyond this, it is generally impossible to complete such complex planning in the ED setting.…”
Section: Initiating Planning In the Patient Approaching End-of-lifementioning
confidence: 99%